Women in the traditional culture of the Bizeljsko and Kozjansko regions - Svetieva, Aneta (Etnolog. Nova vrsta (Ljubljana), 2001)
The position of a woman in the Bizeljsko and Kozjansko regions in the first half of the 20th century depended on her position in the family and household, and this position was directly related to the virilocal residence, property and legal relations, and to the system of authority in the traditional village society. The clear divisions by sex and age in the family as well as in society were very significant in this sense. Women were under the massive pressure of social control. A girl's or woman's future also depended on the social and property differences. Nevertheless, it appears thatin these two areas women managed - by making the most of wisdom, female diplomacy, instinct and shrewdness - to run their households without endangering the traditional model of the village community in relation to the status of the sexes in which the male principle dominated.
Keywords: Bizeljsko; Kozjansko; Slovenia; Slovenija; 20.st.; položaj žensk; socialni položaj